Alterations of natural killer cells activatory molecules phenotype and function in mothers of ASD children: a pilot study - Saresella, Marina; Marventano, Ivana; Piancone, Federica; Bolognesi, Elisabetta; Hernis, Ambra; Zanzottera, Milena; La Rosa, Francesca; Agliardi, Cristina; Giraldo, Stefano; Chiappedi, Matteo; Guerini, Franca Rosa; Clerici, Mario (Frontiers in Immunology, 2023)
Autism spectrum disorder (ASD) is accompanied by complex immune alterations and inflammation, and the possible role played by Natural Killer (NK) in such alterations is only barely understood. To address this question we analysed activating and inhibitory NK receptors, as well as NK cells phenotype and function in a group of mothers of children who developed ASD (ASD-MO; N=24) comparing results to those obtained in mothers of healthy children who did not develop (HC-MO; N=25). Results showed that in ASD-MO compared to HC-MO: 1) NK cells expressing the inhibitory receptor ILT2 are significantly decreased; 2) the activating HLA-G14bp+ polymorphism is more frequently observed and is correlated with the decrease of ILT2-expressing cells; 3) the CD56 bright and CD56 dim NK subsets are increased; 4) IFN and TNF production is reduced; and 5) perforin-and granzymes-releasing NK cells are increased even in unstimulated conditions and could not be upregulated by mitogenic stimulation. Results herein reinforce the hypothesis that ASD relatives present traits similar to, but not as severe as the defining features of ASD (Autism endophenotype) and identify a role for NK cells impairment in generating the inflammatory milieu that is observed in ASD.